Patient-Derived Fibroblasts With Presenilin-1 Mutations, That Model Aspects of Alzheimer’s Disease Pathology, Constitute a Potential Object for Early Diagnosis - Lopez-Toledo, Gustavo; Silva-Lucero, Maria-del-Carmen; Herrera-Díaz, Jorge; García, David-Erasmo; Arias-Montaño, José-Antonio; Cardenas-Aguayo, Maria-del-Carmen (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD), a neurodegenerative disorder that can occur in middle or old age, is characterized by memory loss, a continuous decline in thinking, behavioral and social skills that affect the ability of an individual to function independently. It is divided into sporadic and familial subtypes. Early-onset familial AD (FAD) is linked to mutations in genes coding for the amyloid-β protein precursor (AβPP), presenilin1 (PS1), and presenilin 2 (PS2), which lead to alterations in AβPP processing, generation of the Amyloid-β peptide and hyperphosphorylation of tau protein. Identification of early biomarkers for AD diagnosis represents a challenge, and it has been suggested that molecular changes in neurodegenerative pathways identified in the brain of AD patients can be detected in peripheral non-neural cells derived from familial or sporadic AD patients. In the present study, we determined the protein expression, the proteomic and in silico characterization of skin fibroblasts from FAD patients with PS1 mutations (M146L or A246E) or from healthy individuals. Our results shown that fibroblasts from AD patients had increased expression of the autophagy markers LC3II, LAMP2 and Cathepsin D, a significant increase in total GSK3, phosphorylated ERK1/2 (Thr202/Tyr204) and phosphorylated tau (Thr231, Ser396 and Ser404), but no difference in the phosphorylation of Akt (Ser473) or the α (Ser21) and β (Ser9) GSK3 isoforms, highlighting the relevant role of abnormal protein posttranslational modifications in age-related neurodegenerative diseases, such as AD. Both 2-DE gels and mass spectrometry showed significant differences in the expression of the signaling pathways associated with protein folding and the autophagic pathway mediated by chaperones with the expression of HSPA5, HSPE1, HSPD1, HSP90AA1, and HSPE1 and reticular stress in the FAD samples. Furthermore, expression of the heat shock proteins HSP90 and HSP70 was significantly higher in the cells from AD patients as confirmed by Western blot. Taken together our results indicate that fibroblasts from patients with FAD-PS1 present alterations in signaling pathways related to cellular stress, autophagy, lysosomes, and tau phosphorylation. Fibroblasts can therefore be useful in modeling pathways related to neurodegeneration, as well as for the identification of early AD biomarkers.